Analysis of DSN MUI Fatwa No. 77/DSN-MUI/VI/2010 Concerning Non-Cash Gold Purchases and Sales - Nurfajri Siswi; Nurjanah Ismail; Yuni Roslaili; Abdul Manan; Muhammad Ash Shiddiqi (Madania: Jurnal Kajian Keislaman, 2025)
This study aims to examine the legal basis and views of Islamic scholars regarding the practice of non-cash gold trading and assess its compliance with Islamic economic principles, particularly regarding the permissibility of such practices as regulated in the DSN-MUI Fatwa No. 77/DSN-MUI/V/2010, considering that gold now has a dual role as an investment tool and a high-value commodity. Using a qualitative methodology through a comprehensive literature review sourced from the Quran, hadith, DSN-MUI fatwa, and inter-school fiqh literature, this study examines in depth the legal arguments that form the basis for the permissibility of non-cash gold transactions. The findings show that DSN-MUI permits such practices with the application of strict conditions, including certainty of ownership, price transparency, and avoidance of usury elements, and this view is in line with the thoughts of some scholars such as Ibn Taimiyah and Ibn Qayyim who provide room for legal adaptation to the development of the modern economic system as long as Islamic principles are maintained. The main contribution of this research lies in the affirmation and integrative argumentation that non-cash gold buying and selling can be justified according to sharia as long as the principles of justice, transparency, and prudence are met, so that this practice is not only consistent with the objectives of sharia to realize benefits and prevent losses, but also relevant in answering the needs of gold transactions in the contemporary era. Penelitian ini bertujuan mengkaji dasar hukum dan pandangan ulama mengenai praktik jual beli emas tidak tunai serta menilai kesesuaiannya dengan prinsip ekonomi syariah, khususnya terkait kebolehan praktik tersebut sebagaimana diatur dalam Fatwa DSN-MUI No. 77/DSN-MUI/V/2010, mengingat posisi emas yang kini memiliki peran ganda sebagai alat investasi sekaligus komoditas bernilai tinggi. Menggunakan metodologi kualitatif melalui kajian pustaka komprehensif yang bersumber dari Alquran, hadis, fatwa DSN-MUI, dan literatur fikih lintas mazhab, penelitian ini menelaah secara mendalam argumentasi hukum yang menjadi dasar diperbolehkannya transaksi emas secara tidak tunai. Hasil temuan menunjukkan bahwa DSN-MUI membolehkan praktik tersebut dengan penerapan syarat-syarat ketat, antara lain adanya kepastian kepemilikan, transparansi harga, serta penghindaran dari unsur riba, dan pandangan ini sejalan dengan pemikiran sebagian ulama seperti Ibnu Taimiyah dan Ibnu Qayyim yang memberikan ruang adaptasi hukum terhadap perkembangan sistem ekonomi modern selama prinsip syariah tetap terjaga. Kontribusi utama penelitian ini terletak pada penegasan dan argumentasi integratif bahwa penjualan beli emas tidak tunai dapat dibenarkan secara syariah selama prinsip keadilan, keterbukaan, dan kehati-hatian terpenuhi, sehingga praktik tersebut tidak hanya konsisten dengan tujuan syariah untuk mewujudkan kemaslahatan dan mencegah kerugian, tetapi juga relevan dalam menjawab kebutuhan transaksi emas pada era kontemporer.